Sistem Integrasi BOT Register Terhadap Website Pengolah Data Menggunakan Akses NGROK - Rizky Parlika; Devan Cakra Mudra Wijaya; Tasya Ardhian Nisaa’; Susy Rahmawati (Jurnal Ilmiah SINUS, 2021)
This information system is based on a website that functions as a data processor obtained from the bot register. The integration of the system uses NGROK access which can unify local public access routes or in one go. The use of XAMPP as a web server can support the use of NGROK. NGROK server has a time duration in one use, which is about 8 hours. Users will get a domain URL when accessing NGROK. This domain URL is so unique that each session will change. The case study we are using leads to the registration system for new members of the East Java Veteran UPN robotics community, which so far still uses Google Form as a means of registering and spreadsheets as data storage media. The need for an innovation which can simplify work, especially during the Covid-19 period, therefore we created an innovation in the form of a bot register that can integrate with the website through NGROK access combined with the MySQL Local Database so that this software is expected to provide access registration directly without having to fear data loss and can also provide secure data management.